Integrationen af psykoterapi og læringsmodeller i et praksisudviklingsperspektiv - Sørensen, Anders Dræby (Slagmark - Tidsskrift for idéhistorie, 2018)
Dominant trends in the evaluation of psychotehrapy are connected to different types of evidence based assessment of various kinds of health technologies, that measure and compare the healing outcome in terms of clinical efficiency. The article is based on a current need for a more nuanced and comprehensive understanding of the psychotherapeutic practice as part of the evaluation of the conceptual and emperical foundations of different therapeutic approaches. Through a historical perspective on the foundation and development of psychotehrapy it is suggested that it is possible to widen such understanding by focusing on psychotherapy as a common name for various related type of learning practices that have different learning objectives. Thus, it is possible to understand cognitivebehavior therapy as a life technology oriented toward cognitive and behavioural unlearning of malpadaptive pathological skills, strategies and patterns of thinking, feeling and behaving for the learning of normal adaptive skills. Existential therapy might be understood as an art of living directed at existential learning of skills for living authentically.